The natural history of asthma - Reed, C. E. (Journal of Allergy and Clinical Immunology, 2006)
Asthma begins most often in infants as wheezing with respiratory infections. If these episodes are mild and infrequent, asthma does not usually persist into the school years. However, if they are more frequent and severe, the asthma is likely to persist. After infancy, incidence falls and continues at about 100/100,000 for the rest of the lifespan. Allergic asthma develops most often in the second decade of life and frequently persists into adult years, but young patients with allergic asthma often enjoy a transient or even a permanent remission. More severe disease and continued allergen exposure cause persistence. Some patients with occupational asthma continue to have asthma long after exposure ceases. Asthma beginning after the fourth decade is usually intrinsic and may include the aspirin triad. Its severity tends to increase with time. Many middle-aged and elderly adults have a persistent decline in lung function that is retarded but not completely prevented by aerosol glucocorticoids. This loss of lung function is often the result of coexisting lung diseases, particularly bronchiectasis and COPD. Patients with asthma have the same overall rate and age of death as the general population, but are more likely to die of lung diseases, including cancer.